NOǴAYLÍLAR DÁWIRINDE TARIYXÍY QOSÍQLAR - Turdıev, B.B. (SCIENCE and SOCIETY, 2026)
In this article, historical poems that have survived from the time of the Golden Horde are analyzed from the point of view of historical sources. The content of the poems in the work "Korakalpog" is not just a dry description, but reflects the way of life of their ancestors, when they lived in alliance with other peoples.